ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN SALAK PONDOH DI PASAR BUAH KOTA LHOKSEUMAWE - Ita Puspita Sari; Cut Putri Mellita Sari (Jurnal Ekonomi Pertanian Unimal, 2019)
The purpose of this study was to know the effect of Salak Pondok Prices, Medan Salak Prices and Income Levels on the Demand for Salak Pondok in the Fruit Market of Lhokseumawe City. This study used primary data sourced from 100 respondents. The data analysis method used in this study was multiple linear regression with the help of Eviews 10. The results of the study showed that Salak Pondok prices had a positive effect on demand, while the Salak Medan prices had a negative effect on demand, and the income levels had an effect positively on demand, but simultaneously, Salak Pondok prices and Salak Medan prices, and income level had a positive effect on the demand for Salak Pondok in the fruit market of Lhokseumawe City and the magnitude of the effect of Salak Pondok prices, Salak Medan Prices and income levels on demand (R2) was 0.5340 (53.40%).